POTENSI ROTAN KAWASAN HUTAN PRODUKSI DI DESA UEKULI KECAMATAN TOJO KABUPATEN TOJO UNA-UNA - Y. Amu, Syaiful Y.; Harijanto, Herman; Sudhartono, Arief; Labiro, Elhayat (Jurnal Warta Rimba, 2021)
In Indonesia, there are eight genera of rattan consisting of approximately 306 species, only 51 species have been used. This means that the utilization of rattan species is still low and limited to species whose benefits are known and sold in the market. It is estimated that more than 516 species of rattan are found in Southeast Asia, originating from 8 genera, namely for the genus Calamus 333 species, Daemonorops 122 species, Khorthalsia 30 species, Plectocomia 10 species, Plectocomiopsis 10 species, Calopspatha 2 species, Bejaudia 1 species and Ceratolobus 6 Of the 8 genera, two rattan genera with high economic value are Calamus and Daemonorops. The purpose of this study was to determine the potential of rattan in the Production Forest Area in Uekuli Village, Tojo District, Tojo Una-Una Regency. This study uses the "survey" method. Plot placement is done intentionally (purposive sampling). Making plots of observations in the field is done by making sample plots in the form of an unbroken measuring line (Continuous Strip Sampling) as many as 100 observation plots. The plot size used is 20 m x 20 m along 1000 meters. The number of observation lines is 2 lines, with the distance between the lines is 200 m. The results found 4 types of rattan, namely stem rattan (Calamus zollingeri Becc), tohiti rattan (Calamus inops Becc), emblem rattan (Calamus ornatus Blume), and ronti rattan (Calamus axillaris Becc). The biggest potential of rattan species is stem rattan (Calamus zollingeri Becc) with a total of 1378 individuals/ha from the total plot. The type of rattan that has the highest Important Value Index (INP) is stem rattan at 83.45%.Keywords: Rattan Potential, Production Forest, Tojo Una-Una Regency.